One of the Tenth - When I was an infant gossips would say when I grew older I'de be a Soldier. - Heath, William, 1795-1840 - also known as Paul Pry ? (McLean, Thomas, 1829)
Scholarly notes may be added at a later date.
Hyde Park, May 27 1829, Sketched at the Review
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain. ? Army. ? Royal Hussars, 10th; Women soldiers -- Caricatures and cartoons